Pengaruh Pembelajaran Matematika dalam Meningkatkan Kemampuan Berpikir Logis Anak Usia Dini di TK Islam Al-Hijrah - Dewi Fitriani; Mita Sari; Mia Nur Ara; Indrika Adam; Sahrini Amir; Miranti Labdulah; Lila Angraini Ponongoa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study examines the role of mathematics learning in improving logical thinking skills in early childhood. The background of this study is based on the importance of logical thinking skills as a foundation for children's cognitive development, which can begin at an early age through appropriate mathematics learning. The purpose of this study is to analyze how mathematics learning can stimulate the development of logical thinking in early childhood and explore effective learning strategies. The methods used are library research and observation of several models of mathematics learning for early childhood in early childhood education institutions. The findings indicate that fun and concrete activity-based mathematics learning can improve children's abilities in critical thinking, constructing patterns, drawing conclusions, and solving simple problems. The implications of this study emphasize the need for the application of creative and interactive mathematics learning methods to support the development of logical thinking from an early age, while also encouraging educators to integrate mathematics into children's daily activities. This study also recommends the development of learning media appropriate to children's developmental stages for optimal results.